PENGARUH GAYA KEPEMIMPINAN, TINGKAT PENDIDIKAN, PERILAKU KARYAWAN TERHADAP KINERJA KARYAWAN DI PERUSAHAAN PT. DUMAS TANJUNG PERAK SHIPYARDS SURABAYA - DEWI, NUNING NURNA; AN, ZAHRROH (JEB17 : Jurnal Ekonomi dan Bisnis, 2019)
ABSTRACTThis study was to determine the effect of leadership style variables (X1), education level (X2) and employee behavior (X3) partially influence the performance (Y) of case study employees of PT. Dumas Tanjung Perak Surabaya Shipyards, leadership style variable (X1), education level (X2) and employee behavior (X3) have a simultaneous effect on employee performance (Y) case study of PT. Dumas Tanjung Perak Shipyards Surabaya. This type of research is quantitative. The sample in this study were employees of PT. Dumas Tanjung Perak Shipyards Surabaya with 105 of 316 employees through questionnaires or questionnaires. Data analysis techniques are validity test, reliability test, multiple regression regression coefficient of determination (R2) and correlation coefficient, t test and f test. The results of the study explained that partially the leadership style (X1), education level (X2) and employee behavior (X3) had a partial effect on the performance (Y) of employees had a significant effect, and the results of simultaneous leadership style research (X1), education level (X2 ) and employee behavior (X3) have a partial effect on the performance (Y) of employees having a significant effect and it can be interpreted that H0 is rejected and H1 is accepted.Â Keywords: Effect of leadership style, level of education, employee behavior and employee performance